2020
DOI: 10.1002/ccd.28917
|View full text |Cite
|
Sign up to set email alerts
|

Fixed, high‐volume alcohol dose for septal ablation: High risk with no benefit

Abstract: Expert Article Analysis for:Outcomes of hypertrophic obstructive cardiomyopathy patients undergoing alcohol septal ablation with a standard 3 mL dose of ethanol: Focus on long-term safety Fixed, high-volume alcohol dose for septal ablation: High risk with no benefit Key Points• Alcohol volume is positively correlated with mortality following alcohol septal ablation (ASA).• Over time, there has been a trend to use lower volumes of alcohol for ASA. Most cases can and should be performed using 1-2 cc of alcohol.•… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…This finding is in line with results of previous studies that demonstrated a positive correlation between alcohol dose and subsequent myocardial biomarker release indicative of the amount of myocardial necrosis [11,26,27]. Thus, from the clinical point of view, an effort to minimize the final post-ASA myocardial scar by using lower doses of alcohol might lead to insufficient tissue ablation and increased need of repeated ASA or myectomy [3,11,28]. Conversely, a more aggressive approach might reduce repeated procedures.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with results of previous studies that demonstrated a positive correlation between alcohol dose and subsequent myocardial biomarker release indicative of the amount of myocardial necrosis [11,26,27]. Thus, from the clinical point of view, an effort to minimize the final post-ASA myocardial scar by using lower doses of alcohol might lead to insufficient tissue ablation and increased need of repeated ASA or myectomy [3,11,28]. Conversely, a more aggressive approach might reduce repeated procedures.…”
Section: Discussionsupporting
confidence: 90%